EVALUASI FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN PPh ORANG PRIBADI (AKUNTIA JURNAL Jurnal Akuntansi, Terpercaya, Menginspirasi dan Asli, 2017)
The purpose of this study is to evaluate factors influencing acceptance of personal people income tax ( PPH OP) during range of time 2004-2006 as well as giving solution concerning efforts able to be done to increase. The analysis method that used is descriptive technique with model of interaktif. From result of data analysis indicate that factors influencing acceptance of PPH OP is too high tariff, Notice ( impractical and complicated SPT) and also tax officer image which have come too far unintentionally expand ugly in society. To overcome the problems, require to performed a taxation socialization and counselling intensively with a purpose so that taxpayer understand and comprehend applied governments policy about tariff and SPT and also to vanish ugly image of tax officer expanding in society so that acceptance of PPH OP can reach maximally.